PENERAPAN TEKNOLOGI TERUMBU BUATAN DI PERAIRAN LAUT PULAU ABANG, BATAM - Setiawan, Iwan Eka (Jurnal Hidrosfir Indonesia, 2009)
The application of artificial reef technology has been done on Abang Island, Batam were conducted on Juni-October 2007. The research objectives are to enhance the fish population and rehabilitate marine environment in Abang island waters. The activities are particularly in assessment site selection survey for development the artificial reef, contruction and deployment of 10 unit the artificial reef at the selected sites. Parameter measured were: bathymetri, water quality aspects, current and sedimentation.The results of the assessment for marine environment condition have seen the water qualities such as temperature, salinity, dissolved oxygen in the normal condition and they conduct as not as unlimited factors for artificial reef program. In other hand, the assessment of sea bed morphology have seen homogen marine topography with slope slightly, the dominant of sediment seabed is sandy beach. The deployment sites have to be selected at 3 positions are surrounded 0o 30’28.47” N ; 104o 16’ 5.55” E, range 20-25 meter and calm waters (low current flows).